Barriers to adopting solar photovoltaic systems in Hong Kong. Issue 5 (August 2018) - Lo, Kevin; Mah, Daphne Ngar-Yin; Wang, Guihua; Leung, Michael KH; Lo, Alex Y; Hills, Peter
The adoption of solar photovoltaic systems is often constrained by various sociotechnical barriers. In this paper, we identify and differentiate barriers to photovoltaic among three groups of potential adopters in Hong Kong: individuals, businesses, and the public sector. A total of 55 interviews were conducted to collect the data for the study. The results indicate that the most important constraints were technical barriers such as space limitations and low energy output, followed by economic barriers such as high upfront costs and long payback periods. Furthermore, we found that individuals were the group most exposed to market, policy, and regulatory barriers and they had to contend with the highest number of barriers. Our analysis also illustrates that there was a close interrelationship between the barriers. For example, technical barriers, such as space limitations, could be overcome partially by addressing regulatory barriers. Based on the analysis, we formulate a number of policy recommendations. The results of this study could be useful to the government in its attempt to facilitate a sustainable energy transition in Hong Kong.